Pengembangan Media Pembelajaran Digital Administrasi Perpajakan Di SMK Negeri 2 Batam - Robby Krisyadi; Ricky Ricky (Universitas Internasional Batam, 2021)
The aim of designing digital-based learning media is to help overcome the obstacles experienced by SMKN 2 Batam which is caused by the COVID-19 pandemic outbreak which has forced teaching and learning activities in schools to be carried out online. This situation of course creates an uncommon feeling for students, parents, and especially teachers due to unpreparedness of facilities, infrastructure and human resources in carrying out teaching and learning activities online. Before starting the design of instructional media, the authors conducted discussion and direct observation with Mrs. Dian as the representative of SMKN 2 Batam to understand the situation and activities of online teaching and learning activities carried out by SMKN 2 Batam. This learning media has been designed to provide modules and power points containing material and practice questions tailored to the KIKD in the Tax Administration subject so that teachers and students only need to use them when online learning and teaching activities are in progress. Through the process of implementing work results, the process of online learning and teaching activities will be better with digital learning media applied at SMKN 2 Batam. These results also show that well-designed learning media will support students in mastering the subject matter during online learning and teaching activities.